Acute presentation of thrombocytopaenia in systemic lupus erythematosus is associated with a high mortality in South Africa. (February 2014) - Patel, N; Mody, GM
The objective of this study was to determine the pattern of presentation, response to treatment, and outcome in patients with systemic lupus erythematosus (SLE) and thrombocytopaenia (TCP). A retrospective review of the records of patients with SLE and TCP and a matched control group of SLE patients without TCP, seen in the rheumatology department in Durban, South Africa, was performed. The demographic data, clinical findings, laboratory findings, treatment and outcome were recorded. There were 54 patients and an equal number of controls. They comprised 30 Indians and 24 African Blacks, median age of 33 years and female to male ratio 5.8:1. A group of eight patients who initially presented with idiopathic thrombocytopaenic purpura (ITP) and subsequently developed SLE were analysed separately. An acute presentation was noted in 31 patients (57%). Patients with an acute presentation had an increased prevalence of renal disease (77% vs 43.5%; p  = 0.01) and an increased number of deaths (38.7% vs 4.4%; p  = 0.004). The majority of patients responded to corticosteroids (68.5%) and splenectomy. There was an increased prevalence of renal disease ( p  = 0.03) and deaths ( p  = 0.004) among patients with TCP. The majority of deaths had an acute presentation ((12/13; 92.3%) ( p  = 0.004)), and were due to infection and active lupus. TCP with an acute presentation is associated with a high mortality and predicts survival in SLE.